Buccal fat pad as an intra oral reconstruction method in a case of oral verrucous carcinoma (Update Dental College Journal, 2018)
The buccal fat pad is a special type of fat tissue, which is located anterior to the masseter muscle and deep to the buccinator muscle. It provides gliding motion between muscles, protects the neurovascular bundles from injuries and maintains facial convexity. The use of the buccal fat pad is promoted for the reconstruction of postsurgical intraoral defects in verrucous carcinoma because of its easy to harvest and rich in vascular supply. Here we present a case of 65 years old male with verrucous carcinoma of left buccal mucosa and retro molar trigone came to the Department of Oral & Maxillofacial Surgery, Dhaka Dental College & Hospital, Dhaka, Bangladesh which was successfully managed by surgical excision of lesion and reconstruction with buccal fat pad.Update Dent. Coll. j: 2018; 8 (2): 26-29